Recent progress of Y‐series electron acceptors for organic solar cells - Bing Lu; Jian Wang; Zhecheng Zhang; Jin Wang; Xiaolei Yuan; Yue Ding; Yang Wang; Yong Yao (Nano Select, 2021)
Abstract Organic solar cells (OSCs) have entered the era of non‐fullerene electron acceptors. Nowadays with the rapid development of non‐fullerene electron acceptor materials, Organic photovoltaic show huge potential in challenging conventional photovoltaic technology. Among the emerging non‐fullerene electron acceptors, the Y‐series acceptors own superior performance. The single‐junction devices based Y‐series acceptors have achieved power conversion efficiencies of 17∼18%. This paper gives an overview of the recent advances of Y‐series electron acceptors. Through discussing the selected molecules, the perspective of molecular design on three parts of the molecules, including the central core, side chain and end group, are spotlighted, and the photoelectric properties, photovoltaic performance and film morphology of various Y‐series acceptors materials are also presented. Finally, some molecule design directions will be proposed to further promote the progress of OSCs.